The Yaya Reserve: From the Evolution of its Plant Cover to Proposals for Sustainable Management - Jean-Marc Zaouri, Bi Gala; Eblin, Marc Olivier; Guede, Cataud Marius; Kouadio, Bob Kouakou (European Scientific Journal, ESJ, 2024)
The Yaya reserve, one of the biodiverse forests in Ivory Coast, faces significant threats from agricultural colonization, illegal logging, and demographic pressure, which could jeopardize its sustainability. This paper focuses on contributing to the reserve’s sustainable management. To achieve this, three categories of data were collected: remote sensing data, floristic inventory data, and survey data from the neighboring populations. Remote sensing data were obtained by downloading images from the USGS earth explorer website. Floristic data were obtained through surface and itinerant survey. Survey data were collected using a structured interview. The images were processed to calculate the areas of various land use classes. The floristic data were analyzed for species richness and composition, while the survey data were analyzed to understand local perceptions of landscape dynamics, current management practices, and proposals for participatory management. The results revealed two major periods in the forest’s dynamics: increased deforestation from 1986 to 2005 and subsequent restoration from 2005 to 2022. These phases of degradation and restoration are likely related to recent social and political crises and management challenges. The floristic inventory identified 167 woody species across 134 genera and 47 families. 24 species (14% of the total) are endemic to West Africa, and 21 species (12.42%) are listed on the IUCN red list, indicating a relatively good conservation of the forest. The survey data highlighted the vulnerability of the forest and underscored the importance of centralized decision-making in management. The study suggests that participatory management could be a viable alternative for protecting the reserve. The hypotheses clearly states that the active involvement of local populations in the sustainable exploitation of forest resources can improve living standards, while helping to preserve the forest from exploitative practices.